Analisa Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian Produk Rokok Pada Anak Usia Jenjang Remaja - Hidayati, Novi Itsna; Umam, Khotibul; Lidyana, Novita (Agrotechbiz : Jurnal Ilmiah Pertanian, 2022)
This research aims to find out which product, price, place and promotion factors are most important for consumers in making the decision of buyers of cigarette products.The population of this study is people who become consumers who consume cigarette products, while the samples taken are 100 respondents of adolescent age children aged 17 to 21 years. This type of research is quantitative research. Data analysis uses multiple linear regression analysis. The results of the analysis of the research data indicate that the factors of product, price, place and promotion have a significant effect on the decision of cigarette buyers by adolescents. The magnitude of the effect of product variables, price, promotion and place on the decision to purchase cigarette products by 30.5%. While the remaining 69.5% is explained by other variables not examined in this study.Keywords: consumer behavior, promotion, purchase decision